2022
DOI: 10.1111/andr.13327
|View full text |Cite
|
Sign up to set email alerts
|

Examining potential mechanisms of testicular fibrosis in Klinefelter Syndrome: A review of current understanding

Abstract: Background Men with Klinefelter Syndrome develop some degree of seminiferous tubule degeneration, hyalinization, and fibrosis by adulthood. However, the pathophysiology surrounding testicular fibrosis in Klinefelter Syndrome patients remains incompletely understood. Objectives To perform a systematic review of literature studying the mechanisms of fibrosis initiation or propagation in Klinefelter Syndrome testes. Materials/methods PubMed was searched systematically for articles specific to Klinefelter Syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In addition to changes in the vasculature and the blood–testis barrier (BTB), previous studies of KS testes have identified an increased number of immune cells and increased inflammation as the possible foundation for the observed testicular fibrosis ( D'Aurora et al , 2015 ; Willems et al , 2020 ; Bradshaw et al , 2023 ). Cell-specific changes in gene expression pointed towards an increased signaling interaction strength of both macrophages and MCs in KS and NOA compared to CTRLs, and a marked increase in the incoming lymphocyte interaction strength in KS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to changes in the vasculature and the blood–testis barrier (BTB), previous studies of KS testes have identified an increased number of immune cells and increased inflammation as the possible foundation for the observed testicular fibrosis ( D'Aurora et al , 2015 ; Willems et al , 2020 ; Bradshaw et al , 2023 ). Cell-specific changes in gene expression pointed towards an increased signaling interaction strength of both macrophages and MCs in KS and NOA compared to CTRLs, and a marked increase in the incoming lymphocyte interaction strength in KS.…”
Section: Discussionmentioning
confidence: 99%